Mapping and Clustering of Cultural Heritage Using Fuzzy Logic Approach in Heritage City of Parakan, Central Java, Indonesia - Bahri, Saeful; Purwantiasning, Ari Widyati (International Journal of Architecture and Urbanism, 2025)
This research is a part of multi-year research, which started in 2022 by conducting some studies, either literature or simulation, for heritage trails within historical areas. In supporting the primary research of the implementation of Heritage Trail’s concept within Historical Areas, this research was also delivering the analysis of mapping and clustering of cultural heritage through Heritage Trail’s Guidelines to designate the appropriate cluster of cultural heritage within the historical area, particularly in the Heritage City of Parakan, Central Java, Indonesia. Using a fuzzy logic approach, this research has analyzed the relevant cultural heritage cluster within the historical area of Heritage City of Parakan, Central Java, Indonesia. It has been proposed, together with another study result, to be an appropriate cluster. Thus, this research has completed some of the Heritage Trail’s basic principles to support the need to design the Heritage Trail within the Heritage City of Parakan, Central Java, Indonesia.